Muaragembong: Potensi alam dan olahan Dodol Pidada dalam video dokumenter - Sri Hapsari Wijayanti; Agnes Harnadi; Putra Putra; Toyomi Sayagiri; Aditha Thomas; William Frederich (Riau Journal of Empowerment, 2019)
Not many people know the potential of Muaragembong Sub-District, Bekasi, West Java. The skills to process pidada mangroves, in particular, should be introduced to the people who also live in areas with the same mangrove forest wealth as Muaragembong. The purpose of this activity is to design a documentary video about the activities of a coastal woman who produces dodol pidada. The video, which titled "Cara Praktis Produksi Dodol Pidada, Olahan Top Kampung Beting, Desa Pantai Bahagia, Kecamatan Muaragembong, Bekasi, Jawa Barat / Practical Ways of Pidada Dodol Production, Processed Top Kampung Beting, Pantai Bahagia Village, Muaragembong District, Bekasi, West Java" design through the three stages: pre-production, production, and postproduction. This 09.40 video has been tested on thirty respondents via a google form. The results are that this video was considered adequate in terms of sound quality (43.3%), images (43.3%), transitions between images (50%), choice of music (43.3%), and duration (46.7%). This video contains excellent inspirational impressions (33.3%) and good in terms of content (40%), visual (48.3%), and font size (30%). The presence of this video can use a learning media to give skills how to process pidada fruits become dodol pidada easily and safely. In addition, this video is a promotion of the marine tourism potential of Muaragembong, which has been less exposed. No less important, this video is expected to inspire Indonesian women to become strong entrepreneurs.